2002
DOI: 10.1021/la0259499
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Liquid-Crystalline Gel Formation in a Room-Temperature Ionic Liquid

Abstract: Addition of water to 1-decyl-3-methylimidazolium bromide is shown to result in its spontaneous selforganization and the concomitant formation of a liquid-crystalline gel, thus providing a simple means of preparing a supramolecular assembly comprising a room-temperature ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
203
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(214 citation statements)
references
References 17 publications
9
203
1
1
Order By: Relevance
“…Technological developments of so called 'smart' materials are continuously boosting over the whole past decade [1][2][3][4][5][6][7]. Materials are classified as 'smart' if they possess an intrinsic ability to sense and definitely to respond to various external stimuli in a predictable way ( [2] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technological developments of so called 'smart' materials are continuously boosting over the whole past decade [1][2][3][4][5][6][7]. Materials are classified as 'smart' if they possess an intrinsic ability to sense and definitely to respond to various external stimuli in a predictable way ( [2] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The research of these features open new technological vista for various sensors, molecular machines, switches, controllers, etc. Ionic liquids (ILs), or sometimes specifying more precisely -room temperature ionic liquids (RTILs), which, according to definition, are compounds consisting entirely of ions, but in contrast to 'traditional' salts they are liquids already at, or close to, room temperature [8,9], are widely and successfully applied creating multifunctional materials and compositions [3][4][5][6][7]. Selecting combinations of anionic and cationic subsystems one can alter defined physical and chemical properties of RTILs getting possibilities to sense and to control various molecular processes in these media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other techniques such as infrared spectroscopy, X-ray, and neutron diffraction studies have been used to study these ions in the liquid or solid state or at surfaces [6,52,[109][110][111][112][113][114][115][116][117][118][119][120], a real gain in our understanding came with the combination of crystal structure solution, Raman spectroscopy and ab-initio DFT calculations [108,121]. We concentrate the story on the instructive example of the l-butyl-3-methylimidazolium cation, [C 4 mim] þ (see Fig.…”
Section: Brief Introduction To Ab-initio Model Calculationsmentioning
confidence: 99%
“…Davis and his coworkers (Davis et al, 1998) obtained a novel IL by anion metathesis with NaPF 6 after the imidazole-ring miconazole reacting with alkyl iodides to form imidazolium cations, which exhibited lyotropic liquid crystalline behavior while inducing the gelation of benzene. Firestone's group reported that lyotropic liquid crystalline formed in [C 10 mim]Brwater (5-40% wt%) system (Firestone et al, 2002). They also obtained anisotropic gold nanoparticles with a variety of sizes and morphologies in the nanostructured [C 10 mim]Clwater ionogel template by photochemical reduction of HAuCl 4 (Firestone et al, 2005).…”
Section: Ionic Liquid Based Lyotropic Liquid Crystal Systemsmentioning
confidence: 99%